Development of Thermodynamics Learning With Empirical Approach and Portfolio Assessment Techniques - Tineke Makahinda; Vicky Julius Mawuntu (Studies in Learning and Teaching, 2023)
Students face numerous challenges in comprehending thermodynamics concepts and principles. The empirical approach and portfolio assessment technique were used to encourage educators to determine good teaching strategies and motivate students. The purpose of carrying out this research was to develop thermodynamics teaching materials with an empirical approach and portfolio assessment techniques. This research uses a mix method, namely qualitative and quantitative with development research using the Borg and Gall models. This research was conducted on students majoring in Physics Education. Based on the validation results of material experts 91.9% and media expert validation 80.9% that this teaching material is feasible to use. The results of the one-party t-test were given treatment in the learning process, namely an empirical approach with a portfolio assessment technique. Then given a posttest or final test as evaluation material. The data obtained was then processed to test descriptive research data, data normality, hypothesis testing and N-Gain testing with the help of SPSS 22.0 for windows. With an average result 47.25 of pretest and 81.25 of posttest. The N-Gain results are in the medium and high categories and the average result is 0.64 which shows an increase in student results in thermodynamics courses. Students can get information through direct experience, making what they learn more tangible and learning more meaningful and exciting since it helps them to think critically.